Competências profissionais de enfermeiros no contexto obstétrico - Oliveira, Lara Leite (2019)
The present study aimed Analyze the professional skills of nurses working in maternity wards enabled by Rede Cegonha. To do so, he used Patrícia Benner's From Novice to Expert theory, which describes the skills necessary for nurses to become experts in their professional practice, grouped in seven domains, as well as affirming that it is necessary for professionals to go through five stages of development. skills acquisition. It was carried out from November 2016 to November 2019, in qualified maternities and reference for the Rede Cegonha, in four macroregions of the state of Ceará. The professional competence of nurses was assessed by two populations: 22 nurses working in the obstetric context and 440 mothers. The data collection instruments were validated by a group of judges using the Delphi technique. The data were compiled and analyzed statistically using the Statistical Package for the Social Sciences (SPSS) ® version 24.0. Pearson's chi-square and Fisher's exact tests were performed to identify significant differences between maternities. The Kolmogorov-Smirnov test to test the normality of the sample, and the nonparametric test to compare the adequacy of the domains in each evaluated maternity, Kruskal-Wallis. The project was approved by Research Ethics Committees under protocols 1,939,946 and 2,531,361, from Universidade Federal do Ceará and Centro Universitário Católica de Quixadá, respectively. The seven domains described in the theory deal with the following aspects: 1 (Help function), 2 (Teaching and training function), 3 (Diagnosis and Monitoring function), 4 (Effective management of rapidly changing situations), 5 (Administer and monitor therapeutic regimes and interventions), 6 (Monitor and ensure the qualities of practices) and 7 (organizational skills). When comparing the adequacy of the domains in the nurses' self-assessment, it was identified that domain 2 had the best fit (0.90) and domain 4 the worst fit (0.60). Domains 1, 4 and 5 showed a significant difference between maternity hospitals (p <0.05). In general terms, it is clear that Maternity B has the most experienced nurse professionals from the four institutions evaluated. And maternity A presents the least experienced professionals from the four institutions evaluated. It is also inferred that Domain 2 is the most appropriate, in which its skills are understood and applied by nurses. Regarding the evaluation of the mothers, it was identified that the domains 2; 4; 6 and 7 presented the best adjustments (1.00) and domain 5 the worst adjustment (0.56). Domains 1 to 6 showed a significant difference between maternity hospitals (p <0.05). When comparing the adequacy of competences by domains in the view of nurses and puerperal women, it was observed that all domains were better evaluated by puerperal women than by nurses, except for domain 5 (0.56). It is inferred that this is the domain of the worst assessment and what should be reinforced in training and professional qualifications. In general, the best assessed domains were: 2 (The teaching and training function), 6 (Monitoring and ensuring the quality of practices) and 7 (Organizational skills). The association of the adequacy of the domains in the nurses' self-assessment with sociodemographic and professional variables did not show significant results (p <0.05), however in the association of the adequacy of the domains in the assessment of the puerperal women with sociodemographic and obstetric variables, it is found that the domain 5 was influenced by the age group (p = 0.042). Domains 1, 4, 5 and 6 were influenced by income and the presence of a companion (p <0.05). It is concluded, therefore, that the nurses who provide obstetric assistance to the four maternities enabled by Rede Cegonha in the state of Ceará were not considered experts in all the domains described by Benner, despite having been better evaluated in general.